Leucaena leucocephala (Lam.) de Wit seed oil: characterization and uses - Nehdi, Imededdine Arbi; Sbihi, Hassen; Tan, Chin Ping; Al-Resayes, Saud Ibrahim (Elsevier, 2014)
Leucaena leucocephala (Lam.) de Wit (coffee bush) is a strictly tropical species that requires warm temperatures for optimal growth. It is drought-tolerant (even during establishment) and can withstand up to 7 months of dry season. L. leucocephala oil extracted from seeds was analyzed to determine it possible uses. The oil content of the seeds was 5.44% and mainly consisted of linoleic acid (51.65%), oleic acid (21.40%), palmitic acid (13.21%) and stearic acid (5.92%). This oil has high vitamin E activity because of its concentration of α-tocopherol (175.47 mg/100 g). The weak acid and peroxide values (0.6% and 3.56 mequiv.·O2/kg oil, respectively) were indicators of the good quality of the oil. L. leucocephala showed high thermal stability (up to 255.47 °C) and some absorbance in the UV-B and UV-C ranges. The results showed that this new seed oil can be used as an ingredient in cosmetic or pharmaceutical preparations.